Estudo de liberação in vitro e estabilidade de fases sólidas de espironolactona na forma farmacêutica cápsulas - Montanari, Cristina Martiniano (2016)
Spironolactone, a steroidal diuretic, is widely used for the treatment of refractory edema associated with congestive heart failure, hepatic ascites, primary aldosteronism and essential hypertension. Spironolactone presents two polymorphic forms identified as form I and II and five solvates reported in the literature (methanol, ethanol, acetonitrile, ethyl acetate and benzene). It is known that different solid-state forms can cause significant differences in the physicochemical properties of a compound, thus, proper monitoring of solid-state forms, both qualitative and quantitative, is crucial in order to ensure high-quality products. The solvated form was obtained by dissolution of form II in ethyl acetate to obtain saturated solution at room temperature, and the solvent was allowed to spontaneously evaporation. The samples were sieved through stainless steel mesh. The techniques of X-ray diffraction (PXRD), infrared spectroscopy (IR), differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) were applied to characterize the forms. The solubility of spironolactone forms was determined by the equilibrium method. Capsules containing forms II and solvated form were prepared and subjected to dissolution and stability studies (50 ± 1°C). The samples were analyzed using a validated high performance liquid chromatography (HPLC) method. The results of PXRD, DSC and TG analyses showed that the solvated form was successfully obtained in this work. DSC analysis showed endothermic event corresponding to the melting points to both forms and the event related to loss of solvent to the solvated form. TGA analysis showed extensive weight loss to solvated form. Solubility values of form II were statistically higher in all solvents studied. The best in vitro dissolution profile was achieved using pH 4.5 acetate buffer as the dissolution medium with a basket stirrer at 100 rpm. The quantitative determination was performed by HPLC at 230 nm. All validation parameters were satisfactory. The application of the method showed the discriminatory power of the dissolution method. The results also showed the influence on the dissolution and stability properties of the different forms in capsules.